The Influence Of Local Taxes, Local Levies, And The Results Of Separated Local Assets Management On Regency/City Original Revenue In North Sumatra Province 2020-2024 - Muhammad Rafli; Tengku Eka Susilawaty; Puja Rizqy Ramadhan (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the influence of Regional Taxes, Regional Levies, and the Results of Separated Regional Asset Management on Regional Original Revenue (PAD) in Regencies/Cities in North Sumatra Province for the period 2020–2024. The study uses a quantitative associative approach with a multiple linear regression method. The study population covers all 33 Regencies/Cities in North Sumatra with a total of 165 budget realization reports, using a saturated sampling technique. The data used are secondary data obtained from budget realization reports through the official government website. The results of the study indicate that partially Regional Taxes, Regional Levies, and the Results of Separated Regional Asset Management have a positive and significant effect on PAD. Regional Taxes are the largest contributors, especially from Motor Vehicle Tax, Motor Vehicle Ownership Transfer Fee, Motor Vehicle Fuel Tax, and hotel and restaurant taxes. Regional Levies contribute through payments for certain services and permits. Meanwhile, the Results of Separated Regional Asset Management, such as Regionally-Owned Enterprises (BUMD) and regional strategic assets, contribute through dividends, asset rentals, and operating profits. Simultaneously, these three variables significantly influenced PAD, with a coefficient of determination (R²) of 86.3%. This indicates that most of the variation in PAD can be explained by these three variables. This study emphasizes the importance of optimizing PAD sources to increase fiscal independence and support sustainable regional development.